2018
DOI: 10.19277/bbr.15.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of human hind limb massage by analysis of Laser Doppler Flowmetry and Photoplethysmography signal components using the wavelet transform

Abstract: Biomedical and Biopharmaceutical Research J o r n a l d e I n v e s t i g a ç ã o B i o m é d i c a e B i o f a r m a c ê u t i c a 70 Comparing the effects of human hind limb massage by analysis of Laser Doppler Flowmetry and Photoplethysmography signal components using the wavelet transformComparando os efeitos da massagem no membro inferior humano através da análise dos componentes dos sinais de Fluxometria de Laser Doppler e de Fotopletismografia utilizando a transformada de wavelet Abstract Non-invasive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…Mais recentemente, tam-culatory homeostasis likely involving some cross-talk between local neurogenic and myogenic mechanisms central components via sympathetic efferents. Recently we found that massage in one inferior limb could induce a similar circulatory adaptation interfering with the circulatory homeostasis of both limbs 15 , confirming the same type of cooperation phenomena between limbs described previously. All these observations were obtained with non-invasive techniques, namely laser doppler flowmetry (LDF) and photopletismography (PPG), well known and experimented techniques, although not exempt from criticism and concerns 4,12,16 .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mais recentemente, tam-culatory homeostasis likely involving some cross-talk between local neurogenic and myogenic mechanisms central components via sympathetic efferents. Recently we found that massage in one inferior limb could induce a similar circulatory adaptation interfering with the circulatory homeostasis of both limbs 15 , confirming the same type of cooperation phenomena between limbs described previously. All these observations were obtained with non-invasive techniques, namely laser doppler flowmetry (LDF) and photopletismography (PPG), well known and experimented techniques, although not exempt from criticism and concerns 4,12,16 .…”
Section: Introductionsupporting
confidence: 89%
“…Em ambos os casos esta cooperação parece revelar outros intervenientes na homeostase circulatória na zona distal do membro, envolvendo provavelmente alguma comunicação entre os componentes centrais dos mecanismos neurogénicos e miogénicos locais, através de eferentes simpáticos. Recentemente, descobrimos que a massagem, efetuado num membro inferior, podia induzir uma adaptação circulatória similar, interferindo com a homeostase circulatória de ambos os membros 15 , confirmando o mesmo tipo de fenómeno de cooperação entre membros descrito acima. Todas estas observações foram obtidas com técnicas não invasivas, nomeadamente fluxometria por laser Doppler (FLD) e fotopletismografia (FPG), técnicas bem conhecidas e testadas, mas não isentas de críticas e preocupações 4,12,16 .…”
Section: Methodsunclassified
“…Nevertheless, this common perfusion response registered in both limbs, and in particular, in the resting foot after evoking the VAR in the opposite foot does suggest a centrally-mediated neurogenic response. Recent studies applying this methodology, reported similar phenomena in human (Rocha et al, 2017 , 2018 ) as in mice (Monteiro Rodrigues et al, 2018 ). Although we cannot conclude that this response is adrenergic in nature or not, it is likely evoked by the abruptly intense myogenic and endothelial cooperation registered in the depending limb and is a response to regulate the regional circulation physiology.…”
Section: Discussionmentioning
confidence: 59%
“…Data were collected from participants included in previous studies regarding perfusion of the human lower limb, sharing specific predefined inclusion/non-inclusion criteria [33][34][35][36][37][38][39][40]. Participants were all non-athletes reporting regularly low physical activity and absence of any metabolic disease (diabetes, dyslipidaemia).…”
Section: Participantsmentioning
confidence: 99%
“…We have detected baseline perfusion asymmetries in healthy participants, of both sexes and different ages, submitted to different procedures meant to (temporarily) modify peripheral perfusion in the lower limb. From massage [33][34][35] to the venoarteriolar reflex [36], plantar flexion [37], unipodal squat/hemisquat, and walking [38,39], we were able to identify and follow each hemodynamical adaptive process impacting not only local perfusion but also systemic hemodynamics in humans as in mice [36,40]. Therefore, the aim of the present analysis was to collectively assess the association of sex, age, and body mass index (BMI) with perfusion asymmetries at rest and in the recovery period after a controlled challenge from the studies published previously by our group (Table 1).…”
Section: Introductionmentioning
confidence: 99%